El progreso social en Bolivia: Un análisis departamental - Luis Fernando Serrudo; Carlos Gustavo Machicado; Juan Cristóbal Birbuet (Institute for Advanced Development Studies (INESAD), 2019)
– This study calculates the Social Progress Index (SPI) for the 9 Departments of Bolivia during the period 2012-2016. The indicators have been calculated by using secondary information from official sources. We observe that the Departments of Santa Cruz and Tarija are the ones that have the highest level of social progress, while Potosí and Pando are the most lagging. We show that the departmental SPI has correlation with the GDP per capita, the monetary poverty index and the index of unsatisfied needs, but it has a low correlation with the Human Development Index (HDI) and no correlation with public investment per capita.
Keywords: C81; I30; R11; 330; microeconomic data; welfare and poverty; regional economics